The Protective Effects of Melatonin Against LPS-Induced Septic Myocardial Injury: A Potential Role of AMPK-Mediated Autophagy - Di, Shouyin; Wang, Zheng; Hu, Wei; Yan, Xiaolong; Ma, Zhiqiang; Li, Xiaofei; Li, Weimiao; Gao, Jianyuan (Frontiers in Endocrinology, 2020)
Melatonin, an indolamine secreted by the pineal gland, as well as most of the organs and tissues, provides a strong defense against septic myocardial injury. However, the underlying mechanism has not been fully illustrated. In this study, we investigated the protective effects of melatonin against lipopolysaccharide (LPS)-induced myocardial injury as well as the mechanisms involved. Mice were intraperitoneally injected with LPS to induce a septic myocardial injury or an LPS shock model, depending on the dose of LPS. Melatonin was given (20 mg/kg/day, via intraperitoneal injection) for a week prior to LPS insult. 6 h after LPS injection, echocardiographic analysis, TUNEL staining, transmission electron microscopy (TEM), western blot, quantitative real-time PCR and ELISA were used to investigate the protective effects of melatonin against LPS induced myocardial injury. AMPK inhibitor, autophagy activator and inhibitor, siRNAs were used for further validation. Survival test showed that melatonin significantly increased the survival rate after LPS shock. In the sepsis model, melatonin markedly ameliorated myocardial dysfunction, decreased the release of inflammatory cytokines, activated AMP-activated protein kinase (AMPK), improved mitochondrial function, and activated autophagy. To confirm whether the protection of melatonin was mediated by AMPK and autophagy, Compound C, an AMPK inhibitor; 3-MA, an autophagy inhibitor; and rapamycin (Rapa), an autophagy activator, were used in this study. AMPK inhibition down-regulated autophagy, abolished protection of melatonin (as indicated by significantly decreased cardiac function), increased inflammation and damaged mitochondrial function. Furthermore, autophagy inhibition by 3-MA significantly impaired the protective effects of melatonin, whereas autophagy activation by Rapa reversed LPS + Compound C induced myocardial injury. In addition, in vitro studies further confirmed the protection of melatonin against LPS-induced myocardial injury and the mechanisms involving AMPK-mediated mitochondrial autophagy signaling. In summary, our results demonstrated that melatonin protects against LPS-induced septic myocardial injury by activating AMPK mediated autophagy pathway.